Impact of Tanda Dam on Agriculture Land use and Cropping Pattern: (A Case Study of Mouza Kalochanna District Kohat) - Saeed Khan, Anwar; Nasir, Jamal; Haq, Fazlul (The Journal of Humanities & Social Sciences, 2023)
The present paper deals with the impact of Tanda Dam located inKohat District on Agriculture land use and cropping pattern in Mouza Kalochanna. The study is based on two sets of data (2005-06 and 2011-12) collected from Revenue Office Kohat district. The data of 2005-06 were selected because the Dam was closed and the water was not available for irrigation in 2005-06, while in 2011-12 it was reopened for irrigation. Data was collected and analyzed to determine the trends and dynamics of agriculture land use and cropping pattern. The findings reveal that most of the cultivated land was current fallow in both cropping seasons in2005-06, while in 2011-12 the cultivated land increased than the current fallow in both cropping seasons. This shows the impacts of Tanda Dam on agriculture land use and cropping pattern.